2017
DOI: 10.1016/j.ajur.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of surgical complications in the elderly: Can we improve outcomes?

Abstract: As the number of Americans aged 65 years and older continues to rise, there is projected to be a corresponding increase in demand for major surgeries within this population. Consequently, it is important to utilize accurate preoperative risk stratification techniques that are applicable to elderly individuals. Currently, commonly used preoperative risk assessments are subjective and often do not account for elderly-specific syndromes that may pose a hazard for geriatric patients if not addressed. Failure to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 46 publications
1
18
0
2
Order By: Relevance
“…In order to deliver this aim, it is necessary to include a preoperative risk stratification using a frailty index, for example the ASA score, and cardiopulmonary exercise testing for patients undergoing intra-abdominal surgery, preoperative management of iron deficiency and anemia, and preoperative exercise intervention. Most studies come to the conclusion that further proof is needed of the utility and validity for improving surgical outcomes through advances in preoperative care 8,24 .…”
Section: Assessment and Optimization Of Preoperative Frailty And Predmentioning
confidence: 99%
“…In order to deliver this aim, it is necessary to include a preoperative risk stratification using a frailty index, for example the ASA score, and cardiopulmonary exercise testing for patients undergoing intra-abdominal surgery, preoperative management of iron deficiency and anemia, and preoperative exercise intervention. Most studies come to the conclusion that further proof is needed of the utility and validity for improving surgical outcomes through advances in preoperative care 8,24 .…”
Section: Assessment and Optimization Of Preoperative Frailty And Predmentioning
confidence: 99%
“…1,8 Bentuk klinis PPC dapat berupa infeksi sistem respirasi/pneumonia, gagal napas (respiratory failure), efusi pleura, atelektasis, pneumotoraks, bronkospasme, sindrom respiratori distres akut (acute respiratory distress syndrome/ARDS), dan pneumonitis aspirasi. 9,10 Berbagai studi menemukan banyak faktor risiko PPC dan mengembangkan model skor prediksi terjadinya PPC, di antaranya skor Arozullah 6,11 dan skor ARISCAT 9 . Studi oleh Widjaya, dkk.…”
Section: Pendahuluanunclassified
“…The elderly patients, especially those with poor functional capacity, are at an increased risk of postoperative pulmonary complications. 5 Previous studies reported preoperative functional capacity to influence postoperative pulmonary complications in patients who underwent lung resection surgery. 6,7 Functional capacity on the 6-minute walking test (6MWT) in patients who underwent lung resection was significantly associated with postoperative pulmonary complications.…”
Section: Introductionmentioning
confidence: 99%